Efektivitas Handout Kingdom Protista Berbasis Siklus Belajar 5E pada Kemampuan Berpikir Kritis Siswa - Yossie Ulfa Nuzalifa; Suci Aulia Putri (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This study aims to analyze and describe the effectiveness of the kingdom Protista handout based on the 5E learning cycle on students' critical thinking skills. This research is a quasi-experimental study with a posttest-only control group design. The population in this study were all students of class X SMA Harapan 3 Medan, while the sample in this study were students of class X MIA A as the experimental class and X MIA B as the control class selected by non-probability sampling using a purposive sampling technique. The data were collected by giving a posttest after the learning process was completed, the instrument used was a critical thinking ability test. The data obtained were analyzed using the independent sample t-test using SPSS software. Based on the research results, the Sig. Levene's Test for Equality of Variances is 0.763, where this value is> 0.05. This means that the variance of the data between the experimental group and the control group is homogeneous or the same. So that the interpretation of the independent sample t-test results table above is guided by the values contained in the "equal variances assumed" table. In the test results above in the equal variances assumed the Sig. (2-tailed) of 0.000 <0.05, this indicates that H0 is rejected and Ha is accepted. Based on these results it can be concluded that the kingdom Protista handout based on the 5E learning cycle is effective in fostering and developing students' critical thinking skills.